2017
DOI: 10.1111/cge.12892
|View full text |Cite
|
Sign up to set email alerts
|

CHARGE syndrome gastrointestinal involvement: from mouth to anus

Abstract: CHARGE syndrome is an autosomal dominant disorder that occurs as a result of a heterozygous loss-of-function mutation in the chromodomain helicase DNA-binding (CHD7) gene, which is important for neural crest cell formation. Gastrointestinal (GI) symptoms and feeding difficulties are highly prevalent but are often a neglected area of diagnosis, treatment, and research. Cranial nerve dysfunction, craniofacial abnormalities, and other physical manifestations of this syndrome lead to gut dysmotility, sensory impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Outcomes for individuals with CHARGE syndrome are typically significantly worse than for those with 22q11.2 DS (Michielon et al, ), suggesting additional factors that separate these syndromes likely influence the clinical course. There are key differences between CHARGE and 22q11.2 DS in terms of the types of airway malformations (e.g., choanal atresia, vascular rings, and tracheobronchomalacia), feeding difficulties, and involvement of cranial nerves IX and X which can impart particular morbidity and mortality among CHARGE patients (K. Blake et al, ; Corsten‐Janssen, Kerstjens‐Frederikse, et al, ; Corsten‐Janssen, Saitta, et al, ; Corsten‐Janssen et al, ; Hudson, Macdonald, Friedman, & Blake, ; Stack & Wyse, ). In combination, these create a particularly high risk of postoperative airway events and aspiration, especially after cardiac surgery (Blake et al, ).…”
Section: Clinical Impact Of Charge On Chd Outcomementioning
confidence: 99%
“…Outcomes for individuals with CHARGE syndrome are typically significantly worse than for those with 22q11.2 DS (Michielon et al, ), suggesting additional factors that separate these syndromes likely influence the clinical course. There are key differences between CHARGE and 22q11.2 DS in terms of the types of airway malformations (e.g., choanal atresia, vascular rings, and tracheobronchomalacia), feeding difficulties, and involvement of cranial nerves IX and X which can impart particular morbidity and mortality among CHARGE patients (K. Blake et al, ; Corsten‐Janssen, Kerstjens‐Frederikse, et al, ; Corsten‐Janssen, Saitta, et al, ; Corsten‐Janssen et al, ; Hudson, Macdonald, Friedman, & Blake, ; Stack & Wyse, ). In combination, these create a particularly high risk of postoperative airway events and aspiration, especially after cardiac surgery (Blake et al, ).…”
Section: Clinical Impact Of Charge On Chd Outcomementioning
confidence: 99%
“…CHARGE syndrome is characterized by craniofacial defects such as orofacial clefting, cranial nerve anomalies and ear deformities (Hsu et al, ; Hudson, Macdonald, Friedman, & Blake, ). Most of these phenotypes are known to be associated with defects in cranial neural crest cell development (Kurosaka, Trainor, Leroux‐Berger, & Iulianella, ; Trainor, ).…”
Section: Charge Syndromementioning
confidence: 99%
“…Several neurocristopathies which also exhibit CA are described in this section in order to show their phenotypic correlations and the possible relationship between defects in neural crest cell development and CA. 2 | CHARGE SYNDROME CHARGE syndrome is characterized by craniofacial defects such as orofacial clefting, cranial nerve anomalies and ear deformities (Hsu et al, 2014;Hudson, Macdonald, Friedman, & Blake, 2016). Most of these phenotypes are known to be associated with defects in cranial neural crest cell development (Kurosaka, Trainor, Leroux-Berger, & Iulianella, 2015;Trainor, 2010).…”
Section: Neurocristopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in the UK that examined infants with CHARGE syndrome found that troubles with constipation caused a need for medication, enemas, and even mechanical stimulation with a rectal probe (Anderzén-Carlsson, 2015). Causes of constipation in this genetic disorder are multifactorial, including abnormal innervation of the GI tract, gastrostomy and jejunostomy tube feeding, a diet limited in texture and food type, as well as maladaptive behaviors around toileting (Hudson, Trider, & Blake, 2017;Hudson, Macdonald, Friedman, & Blake, 2017;Macdonald, Hudson, Ratcliffe, Bladon, & Blake, 2016). Furthermore, children with CHARGE syndrome who are tube fed have been found to have significantly more problems with constipation than those who are orally fed .…”
Section: Constipationmentioning
confidence: 99%